Impact of In-Row Planting Patterns on Reniform Nematodes Using Precision Agriculture in Cotton - David L. Wright; Sheeja George; Ian Small; Theodor Stansly; Zane Grabau (EDIS)
This article is intended to inform cotton producers and associated agricultural professionals of a practical method to help manage plant-parasitic nematodes in cotton. Written by D. L. Wright, S. George, I. Small, T. Stansly, and Z. Grabau, and published by the UF/IFAS Agronomy Department, revised September 2022.